2021
DOI: 10.2174/1389201021666200622121809
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Factor-Mediated Regulation of Active Component Biosynthesis in Medicinal Plants

Abstract: Background: Plants produce thousands of chemically diverse secondary metabolites, many of which have valuable pharmaceutical properties. There is much interest in the synthesis of these pharmaceutically-valuable compounds, including the key enzymes and the transcription factors involved. The function and regulatory mechanism of transcription factors in biotic and abiotic stresses have been studied in depth. However, their regulatory roles in the biosynthesis of bioactive compounds, especially in medicinal pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 166 publications
0
15
0
1
Order By: Relevance
“…Transcription factors (TFs) are critical controllers of functional gene expression in these pathways. In plants, five TF families (AP2/ERF, bHLH, MYB, WRKY, and bZIP) have been reported to be involved in the biosynthesis of terpenoids ( Lu et al, 2016 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors (TFs) are critical controllers of functional gene expression in these pathways. In plants, five TF families (AP2/ERF, bHLH, MYB, WRKY, and bZIP) have been reported to be involved in the biosynthesis of terpenoids ( Lu et al, 2016 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…CAS belongs to the family of OSCs. According to differences in the backbone after cyclization, members of the OSC family can be categorized into CAS, β‐amyrin synthase, dammarenediol synthase, lupeol synthase, and lanosterol synthase (Hou et al, 2021; Wang, Guo, et al, 2021; Wang, Hou, et al, 2021; Wang, Qiu, et al, 2021). In the F. anhuiensis transcriptome, we identified one unigene (unigene6082) encoding the CAS enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Steroidal alkaloids are the major active constituents of Fritillaria L., and more than 100 have been isolated from this genus, accounting for approximately 85% of the total alkaloid content of Fritillaria . Peimine and peiminine contents are frequently used as important criteria for evaluating the quality of Fritillaria L. (Peng et al, 2012; Pi et al, 2009; Shen et al, 2011; Wang, Guo, et al, 2021; Wang, Hou, et al, 2021; Wang, Qiu, et al, 2021). Fritillaria anhuiensis S.C.Chen et S.P.Yin ( F. anhuiensis , Fa), called “Wanbeimu” in Chinese, is an important germplasm resource in the Fritillaria genus.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is speculated that these terpenoids may be regulated by multiple TPS. WRKY transcription factors have been reported to regulate terpenoid production by activating or inhibiting promoter binding of TPS [ 20 , 59 , 60 , 61 ]. In our study, our results showed that 26 members of WRKY were closely related to 34 TPS genes ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%